Domination and Power Relations in Brazilian Agriculture: A Gender Analysis of the Concept of Adequate Food - Tânia Aparecida Kuhnen; Daniela Rosendo (Ethic@: an International Journal for Moral Philosophy)
The main subject of this work is the concept of adequate food defined by the Brazilian Law No 11.346/06, whose implications are here discussed through a gender – especially ecofeminist – lens. The Law defines the right to food that is also considered a fundamental right in the Brazilian Constitution. At the same time, Brazilian economical politics is centered on crops production for exportation in a large-scale agricultural system. Based on that, the following question is addressed in this paper: is the concept of adequate food compatible with the economical privilege attributed to the massive and monoculture agricultural system and factory farms? The aim is to show that they are incompatible and the alternative is a defense of organic family farming and a plant-based diet, as it is presented in the government’s document “Dietary Guidelines for the Brazilian Population” (2014). Another problem that arises from this issue is that agriculture in this large-scale dimension reflects structures of power and domination (Karen J. Warren) and animals used for corpse eating disappears, becoming absent referents (Carol J. Adams). It reflects the structure of a patriarchal society, where men have power over women, animals and plants. The hypothesis is that in family farming women can participate more in the decision making process, reflecting equality and justice in the private sphere. We will analyze the Special Reports on adequate food, mainly the one related to the mission of the Special Rapporteur to Brazil, whose analysis brings information on the gender category. This analysis draws attention on the situation of women in their struggles to fulfill the right to adequate food.